The Princess and the pit stop - Angleberger, Tom (Abrams Books for Young Readers, 2018)
When a Princess learns from her Fairy Godmother that she is in last place in a car race against such fairy tale notables as Humpty Dumpty, the Three Bears, and Rumpelstiltskin, she boldly rebuffs defeat and steps on the gas.